2003
DOI: 10.1038/sj.npp.1300075
|View full text |Cite
|
Sign up to set email alerts
|

Previous Exposure to VTA Amphetamine Enhances Cocaine Self-Administration under a Progressive Ratio Schedule in an NMDA, AMPA/Kainate, and Metabotropic Glutamate Receptor-Dependent Manner

Abstract: Previous exposure to amphetamine (AMPH) in the ventral tegmental area (VTA) enhances cocaine self-administration in a D 1 dopamine receptor-dependent manner. The present study examined the contribution of VTA NMDA, AMPA/kainate, and metabotropic glutamate (mGlu) receptors to this effect. Rats in different groups received three intra-VTA injections, one every third day, of either saline (0.5 ml/ side), AMPH (2.5 mg/0.5 ml/side), AMPH+CPP (NMDA receptor antagonist; 10 mM or 100 mM/0.5 ml/side), AMPH+CNQX (AMPA/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
2
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 60 publications
6
37
2
1
Order By: Relevance
“…In agreement with previous reports (Mendrek et al, 1998;Lorrain et al, 2000;Suto et al, 2002Suto et al, , 2003aVezina et al, 2002), rats in the two exposure groups readily satisfied the self-administration training criteria and did so in similar manner regardless of exposure condition. On average, rats in the two groups satisfied each of the FR1 and FR2 criteria in 1-2 days (Figure 2a).…”
Section: Cocaine Self-administration Trainingsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with previous reports (Mendrek et al, 1998;Lorrain et al, 2000;Suto et al, 2002Suto et al, , 2003aVezina et al, 2002), rats in the two exposure groups readily satisfied the self-administration training criteria and did so in similar manner regardless of exposure condition. On average, rats in the two groups satisfied each of the FR1 and FR2 criteria in 1-2 days (Figure 2a).…”
Section: Cocaine Self-administration Trainingsupporting
confidence: 91%
“…Again consistent with previous reports (Mendrek et al, 1998;Lorrain et al, 2000;Suto et al, 2002Suto et al, , 2003aVezina et al, 2002), rats exposed to systemic AMPH worked more and obtained significantly more cocaine infusions than saline exposed controls when tested under the PR schedule of reinforcement ( Figure 2b). The ANOVA conducted on these data revealed significant effects of exposure (F 1,62 录 14.74, Po0.001).…”
Section: Cocaine Self-administration Testing Under the Pr Schedule Ofsupporting
confidence: 91%
“…The present data showing that the 1 and 7 day deprivation groups show almost identical changes in DA terminal function indicates that these neurochemical effects do not account for the behavioral results. These data, showing a dramatic loss of cocaine effects on DA, are in contrast to accepted theories that equate increased behavioral response to cocaine with increased DA terminal responsiveness (Kalivas and Duffy, 1993;Suto et al, 2003). Previous reports have shown enhanced cocaine-induced DA levels using a variety of other dosing protocols and have associated enhanced DA levels with increased cocaine reinforcement (Vezina, 2004).…”
Section: Discussioncontrasting
confidence: 61%
“…It has also been demonstrated that rats receiving experimenter-administered stimulants, which produces a sensitized locomotor response, acquire selfadministration faster and/or at lower doses (Horger et al, 1990(Horger et al, , 1992Schenk et al, 1991). Animals treated this way also respond to higher breakpoints when subsequently tested on a PR schedule (Mendrek et al, 1998;Lorrain et al, 2000;Covington and Miczek, 2001;Suto et al, 2002Suto et al, , 2003Vezina et al, 2002). Taken together, there appear to be links between locomotor sensitization and sensitization to the reinforcing effects of cocaine.…”
Section: Discussionmentioning
confidence: 98%